2011
DOI: 10.1111/j.1365-2966.2011.19314.x
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping abundance gradients and azimuthal gradients related to the spiral structure of the Galaxy

Abstract: The connection between some features of the metallicity gradient in the Galactic disc, best revealed by Open Clusters and Cepheids, and the spiral structure, has been explored. The step-like abrupt decrease in metallicity at 8.5 kpc (with R0= 7.5 kpc, or at 9.5 kpc if R0= 8.5 kpc is adopted) is well explained by the corotation ring-shaped gap in the density of gas, which isolates the internal and external regions of the disc one from the other. This solves the long-standing problem of a lack of understanding o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
5
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 66 publications
11
136
5
2
Order By: Relevance
“…As discussed in the literature, this is caused by inhomogeneous chemical enhancements in the Galactic disc (Haywood , 2008;Jacobson et al , 2011), orbital diffusion, and radial migration and mixing of OCs (Schönrich & Binney , 2009). These OCs have probably originated from differing Galactic radii and/or from various star forming regions (Lepine et al , 2011). 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the literature, this is caused by inhomogeneous chemical enhancements in the Galactic disc (Haywood , 2008;Jacobson et al , 2011), orbital diffusion, and radial migration and mixing of OCs (Schönrich & Binney , 2009). These OCs have probably originated from differing Galactic radii and/or from various star forming regions (Lepine et al , 2011). 7.…”
Section: Discussionmentioning
confidence: 99%
“…12, a global abundance gradient of +0.002 ± 0.022 dex/kpc is calculated indicating that there is no correlation between [Fe/H] and R GC (kpc) over this wide range. However, the works of Twarog et al (1997), Magrini et al (2009), Lepine et al (2011), andLepine (2013) have shown that abundance gradients correlating [Fe/H] with R GC for OCs should take into account a possible discontinuity at R GC ≈ 8-10 kpc. Figure 13 shows an age-metallicity plot from the corresponding values of our 20 OCs plus those from Dias catalogue.…”
Section: Comparisons Of Morphological and Isochrone Agesmentioning
confidence: 99%
“…The entry shock experienced by the interstellar medium (ISM) gas entering a spiral arm should only exist inside the co-rotation radius, where there is a differential velocity between the spiral pattern speed and the orbital rotation speed of the Galactic ISM. Outside this radius (thought to be just beyond the solar circle in the Milky Way; Lépine et al 2011), supernovae may be the dominant mechanism determining the state of the ISM and, hence, star formation (e.g., Kobayashi et al 2008).…”
Section: Galactic Distributionmentioning
confidence: 99%
“…Sodroski et al (1997) derive a dust temperature gradient with RGC, owing in part to the metallicity gradient in the Galactic disc (Lépine et al 2011) and to variations in the strength of the interstellar radiation field with RGC. The links between these trends and star formation, however, remain tenuous.…”
Section: Introductionmentioning
confidence: 99%